Changing epidemiology and mortality in adult congenital heart disease: looking into the future. (March 2012) - Greutmann, Matthias; Tobler, Daniel
Advances in surgical and medical treatment of children born with congenital heart disease have led to a growing number of adult survivors, particularly to a growing number of adults with complex congenital heart disease. Childhood mortality has continuously decreased over the last few decades and mortality has shifted almost entirely to adulthood. However, most patients are not cured and many remain at risk of premature death. The extent of excess mortality among individual congenital disease entities is not well defined. In this article we outline the current demographics of adults with selected congenital heart lesions. Based on these contemporary patient cohorts, we delineate future changes in patient demographics. A better understanding of these trends may help in the optimal planning of future resource allocation for medical care and optimal planning of multicenter research, for this novel and growing population of young, chronically ill adults.